HAYASHI'S QUANTIFICATION METHOD TYPE III APPLIED TO ADL EVALUATION OF AMBULATION AND TRANSFER - DOMAE, Akira; HAZAMA, Tokuji; MIYAHARA, Hideo (Kodo Keiryogaku (The Japanese Journal of Behaviormetrics), 1980)
In 61 patients with hemiplegia who under a rehabilitation program, the grade of gait disturbance of patient was examined by 6 physical therapists and 6 nurses, respectively. The examination consisted of observation on 46 kinds of gait or related actions; of which 14 were with a handrail, 16 with a cane and 16 with empty hands. Each rater was requested to rate the patient's performance without any mutual discussion but not practical, and practical from the standpoint of ADL(activities of living). The data collected in this way were analzyed by Hayashi's quantification method type III. Both 46 test items and 732 case-raters were arranged according to the similarity, and multidimensional mumerical values were assigned to them, respectively. On 2 dimensional plane spannde by the first 2 components, all 46 test items were plotted on a parabola and, therefore, could be rearranged one-dimensionally. It was suggested that the rank of this new arrangement roughly paralleled to that of the difficulty of the tests, and could be diverted to be utilized for the scaling of the latter. The result of the patient's actual response for the tests, justified the rank of severity proposed by us to be practically satisfactory.